2021
DOI: 10.3390/vaccines9030299
|View full text |Cite
|
Sign up to set email alerts
|

Low Adenovirus Vaccine Doses Administered to Skin Using Microneedle Patches Induce Better Functional Antibody Immunogenicity as Compared to Systemic Injection

Abstract: Adenovirus-based vaccines are demonstrating promising clinical potential for multiple infectious diseases, including COVID-19. However, the immunogenicity of the vector itself decreases its effectiveness as a boosting vaccine due to the induction of strong anti-vector neutralizing immunity. Here we determined how dissolvable microneedle patches (DMN) for skin immunization can overcome this issue, using a clinically-relevant adenovirus-based Plasmodium falciparum malaria vaccine, AdHu5–PfRH5, in mice. Incorpora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Their work also revealed the critical roles of different immune cells performed during the MNA vaccination ( Figure 2 A ) 49 . A similar immune response was observed when applying dissolving MNAs to deliver vaccines against malaria and HIV 50 , 53 , 54 .…”
Section: Mnas Integrated With Living Organismssupporting
confidence: 57%
“…Their work also revealed the critical roles of different immune cells performed during the MNA vaccination ( Figure 2 A ) 49 . A similar immune response was observed when applying dissolving MNAs to deliver vaccines against malaria and HIV 50 , 53 , 54 .…”
Section: Mnas Integrated With Living Organismssupporting
confidence: 57%
“…Flynn et al. [ 30 ] stored dissolving MNs loaded with AdHu5‐PfRH5 vaccine at 25 and 40 °C for up to 6 months. They found that the adenovirus vaccine incorporated into the patch was completely stable at 25 °C, and no vaccine degradation was observed at 40 °C for up to 2 months.…”
Section: Applications Of Mns In Biomedicinementioning
confidence: 99%
“…And the loaded drugs are released when the needles are dissolved or degraded in the body. [30,52] The detail characteristics of these four types of MNs are listed in Table 2.…”
Section: Materials and Classification Of Mnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microneedle systems definitely have great potential to be used as means of immunization against pathogens that affect the mucosal tract. Given the broad advantages these delivery systems own, they are stable at room temperature [77,78,[88][89][90], easy to use, painless and comfortable [91] for the patient, and do not require trained personnel. All these features make them useful when considering mass immunization in a short period of time as required in times of pandemics.…”
Section: Microneedle Arraymentioning
confidence: 99%